GERAKAN BERSAMA (GEBER) MELAWAN TUBERKULOSIS DI WILAYAH KERJA PUSKESMAS SUNGAI BILU BANJARMASIN - Siswadi, Yakobus; Saputra, Bima Adi; Sampepadang, Mega; Chrisnawati, Chrisnawati; Unja, Ermeisi Er; Rahman, Aulia; Oktovin, Oktovin; Warjiman, Warjiman (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2025)
Indonesia is still among the 10 countries with the highest number of tuberculosis cases in the world. Prevention, treatment, and tracing efforts have been carried out, but many new cases are still being found. Handling tuberculosis cases is a shared responsibility and requires cross-sector collaboration. One of the sectors currently involved is the Ministry of Education and Culture, through the Tuberculosis-Aware Schools Program. The TB-Conscious School Program is the embodiment of GEBER towards the elimination of TB by 2030 in educational institutions. Based on coordination with the Sungai Bilu Community Health Center, it was deemed necessary to hold a GEBER event at SMK Wirakrama 1 Banjarmasin. The purpose of this activity was to increase synergy between educational institutions and health services in the context of implementing GEBER through health education and TB detection in school children. The methods used were lectures, demonstrations, and sputum sampling for examination. This activity was attended by 46 students, with males making up the majority at 58%. Based on the evaluation results, there was an increase in participants' knowledge, with the majority (58.7%) scoring “adequate” on the pre-test and 100% scoring “good” on the post-test. The conclusion is that GEBER represents the active participation of various parties in TB management.